2007
DOI: 10.1007/s10162-007-0077-8
|View full text |Cite
|
Sign up to set email alerts
|

Changes in Pitch with a Cochlear Implant Over Time

Abstract: In the normal auditory system, the perceived pitch of a tone is closely linked to the cochlear place of vibration. It has generally been assumed that highrate electrical stimulation by a cochlear implant electrode also evokes a pitch sensation corresponding to the electrode_s cochlear place (Bplaceĉ ode) and stimulation rate (Btemporal^code). However, other factors may affect electric pitch sensation, such as a substantial loss of nearby nerve fibers or even higher-level perceptual changes due to experience. T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

23
145
4
1

Year Published

2008
2008
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 141 publications
(173 citation statements)
references
References 37 publications
23
145
4
1
Order By: Relevance
“…The present study extends these demonstrations of "auditory plasticity" in adult patients to the extreme case, where part of the speech spectrum, the low-frequency acoustic portion, is presented to the "normal" place along the cochlea and the electrically presented speech is shifted (and even severely compressed) to a much more basal location than normal. These findings are also in line with the observations of Reiss et al that the sensations of pitch can change over time in these patients, perhaps driven by the new place-frequency mapping of electrical stimulation [27]. This flexibility of the auditory system to integrate acoustic and electrical information under conditions of distortion and shifting certainly contributes to the success of the Iowa/ Nucleus Hybrid device.…”
Section: Resultssupporting
confidence: 88%
See 1 more Smart Citation
“…The present study extends these demonstrations of "auditory plasticity" in adult patients to the extreme case, where part of the speech spectrum, the low-frequency acoustic portion, is presented to the "normal" place along the cochlea and the electrically presented speech is shifted (and even severely compressed) to a much more basal location than normal. These findings are also in line with the observations of Reiss et al that the sensations of pitch can change over time in these patients, perhaps driven by the new place-frequency mapping of electrical stimulation [27]. This flexibility of the auditory system to integrate acoustic and electrical information under conditions of distortion and shifting certainly contributes to the success of the Iowa/ Nucleus Hybrid device.…”
Section: Resultssupporting
confidence: 88%
“…Recent work from our laboratory has also shown that the pitch sensation associated with a particular Iowa/Nucleus Hybrid electrode can shift over time and that this pitch sensation appears to "migrate" toward the frequencies assigned to that electrode by the patient's everyday listening MAP (a cochlear implant speech processor map that assigns speech frequencies to particular electrodes) [27]. In this experiment, we look more closely at the possible effects of assigning "shifted-fromnormal" speech frequencies to the electrodes of the Iowa/ Nucleus Hybrid implant.…”
Section: Methodsmentioning
confidence: 99%
“…The insignificant effect of pitch-interval size on the differentiation tasks in the present study could be ascribed partly to the channel-setting of sound frequency and/or tone perception changes caused by cochlear implants (Nardo et al, 2007;Reiss et al, 2007).…”
Section: Insignificant Effect Of Pitch-interval Size On Pitch Perceptioncontrasting
confidence: 58%
“…Although patient selection criteria are different between the two groups (with Hybrid patients having more residual hearing), it is still quite interesting to see that very high recognition scores are possible even with a short (10mm insertion, 6 channels in the distal 6 mm) electrode. Reiss et al (2007b) hypothesize that these patients are capable of learning a highly compressed and shifted frequency map over time and that this may correspond to a perceptual change over time in the pitch sensation associated with each electrode (Reiss et al, 2007a). Turner et al (2004) demonstrated, using simulated Hybrid processing of speech presented to normal-hearing subjects, that high-frequency electrical stimulation along with acoustic lowfrequency hearing (as compared to full speech range electric stimulation alone) had the potential to provide a significant advantage for understanding speech in background noise, particularly when the competing signal was other talkers.…”
Section: A+e Results For Speech Presented In Quietmentioning
confidence: 99%